Research on the realization path of China multi-agent value co-creation in new energy microgrids-based on fsQCA method - Yifan Zhang; Hong Chen (Scientific Reports)
Abstract With China’s increasing focus on carbon emissions, photovoltaic power generation (PV) microgrids (MG) have seen remarkable growth in recent years. However, the decline in government subsidies has led to a decrease in the profitability of photovoltaic power generation, making investments in photovoltaics and microgrids less viable. Consequently, enhancing the value for stakeholders in new energy microgrids is crucial for achieving sustainable development, particularly in a subsidy-free context. This research introduces a novel application of Prahalad and Ramaswamy’s value co-creation theory by analyzing 60 microgrids throughout China as case studies. It utilizes the Fuzzy-set Qualitative Comparative Analysis (fsQCA) method to explore the input factors from various stakeholders in new energy microgrids and to identify the pathways that promote value co-creation. The findings reveal three distinct approaches to achieving value co-creation in new energy microgrids, with a notable emphasis on reducing initial capital costs to significantly enhance operational sustainability. The pathway characterized by hard service investment, construction investment, maintenance investment, energy storage investment, and financial support demonstrates the highest explanatory power (coverage 0.443). Conversely, the scenario lacking hard service investment, construction investment, and maintenance investment, while including energy storage investment and financial support, shows lower coverage (0.338) but high consistency, making it applicable in specific situations, such as when policy support is limited.